Vertical Transmission and Discordance of Cytomegalovirus in Twin Pregnancies - Hutton, Jill; Rowan, Paul J. (Frontiers in Cellular and Infection Microbiology, 2021)
Objective The objectives are to estimate the vertical transmission rate in twins relative to singleton pregnancies, to evaluate whether discordance within twin pairs is rare, and to characterize concordance within monozygotic and dizygotic twin pairs in relation to hereditability. Methods We first sought to estimate the vertical transmission rate of congenital CMV infection in twins by gathering cohort-based studies of congenital CMV in which vertical transmission in both singleton and twin pregnancies was reported. This also allowed us to compare singleton and twin infection rates. From the above studies and other large cohorts of congenitally infected infants, the percentage of discordantly infected twin pairs determined whether this is a rare phenomenon. Theorizing discordance is not rare, we then analyzed data from cases with twin outcomes for congenital CMV infection, according to whether the twins were monozygotic or dizygotic, and calculated their corresponding concordance rates to estimate the broad-sense heritability. Lastly, we described other factors that might affect vertical transmission. Results From five articles following at-risk pregnancies, the rate of vertical transmission in twin pregnancies is 58.7% (95% CI 43.3-72.3%) whereas in singleton pregnancies it is 31.4% (95% CI: 29.0-34.0%) p = 0.0002. Of ten studies of larger cohorts of infants with congenital CMV infection, 21 of 42 twin pairs with at least one twin infected were discordant for congenital CMV (50.0%, 95% CI: 34.4–65.6%) indicating discordance of congenital CMV infection in twin pairs is not rare. Of 28 studies covering 37 twin pairs where at least one twin had congenital CMV, and zygosity was known, eleven of thirteen monozygotic twin pairs (84.6%; 95% CI: 53.7-97.3%) were concordant for CMV infection, and nine of twenty-four dizygotic twin pairs (37.5%; 95% CI: 19.6-59.2%) were concordant for infection giving an estimated hereditability of 94.2%. Within these 37 twin pairs, factors such as primary or recurrent maternal infection, prematurity, growth discordance, and sex are described; however, in many of these cases these factors are unknown. Conclusion The rate of vertical transmission of congenital CMV is higher for twins than singletons. Discordance of congenital CMV in twins is not rare and suggests a possible genetic susceptibility to congenital CMV.